The Most Important Medical Theories and Works of Abu Sahl Masihi, an Iranian Scientist during the Golden Civilization of Islam - memariani, Zahra; Hashemimehr, Mohammad (Universitas Islam Negeri Raden Intan Lampung, 2023)
Abu Sahl Masihi is a physician, philosopher, mathematician, and famous astronomer of the first half of the 11th century AD. Some scientists have written that Abu Sahl was the master of Avicenna.This study aims to introduce him by using the most important medical theories and works of Abu Sahl Masihi.This library study has been carried out among the most important medical works of Abu Sahl Masihi. Common searches were performed on valid databases and papers. Abu Sahl did not agree with the detailed description of the treatment issues. He focused on the scientific and theoretical part of medicine including General basics and principles of prevention. In his medical works, Abu Sahl has explained the theoretical part in order and simply and the therapeutic part briefly. He has rejected other physicians' opinions that considered menstrual bleeding to be fetal food and thus ending it during menopause as a reason for termination of pregnancy and said that such blood that the body repels cannot be the source of fetal food. He considered the healthy blood of the mother's body as the source of fetal food. Like Aristotle, Abu Sahl has regarded the heart as the life force center, innate heat, and vital spirit. He also had a significant view of the heart structure and the vessels connected to it. We can introduce Abu Sahl as one of the pioneers of the theory of the beginning of digestion of food through the mouth due to being impregnated with saliva by the enzymes in the secretions of the digestive system. Despite the importance of Abu Sahl’s works, his writings have been less considered. It seems that more research on the noteworthy ideas of this great scientist is needed by scholars and researchers.